A identidade do sacerdote católico- Um estudo sobre o celibato e a política de identidade da Igreja Católica - Kiyan, Ana Maria Mezzarana (2005)
The present research is aimed to analyze the metamorphosis in identity (Ciampa, 1996) of the priests who belong to the Roman Apostolic Catholic Church, by giving a special consideration to the celibacy as a meaningful element in the identity policy (Ciampa, 2002) of the institution concerning its clergy, both from the discipline and dogma point of views, all with a social psychology approach. Although the major concern of the research is to talk over the present situation, understanding the process that has set the ecclesiastic celibacy along Catholic Church history is necessary. Thus, the set up of celibacy will be mentioned only to clarify the way it works. Hence, it is a study with no theological basis. The research procedures were contextualized surveys on the historical/social aspects where the situation develops as well as a collection and further analysis of interviews carried out with priests and/or former priests who were for and against the practice of celibacy, with their lives later analyzed under a social psychology approach.